2002
DOI: 10.1080/00223980209605547
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Emotional Stroop Task: Examining the Paradox of Measurement Change

Abstract: The Emotional Stroop (ES) task (I. H. Gotlib & C. D. McCann, 1984) has been proposed as an experimental measure to assess the processing of emotion or the bias in attention of emotion-laden information. However, study results have not been consistent. To further examine its reliability for empirical research, the authors of this study administered the ES task to 33 participants on 2 separate occasions separated by 1 week. Results indicated that retest reliabilities for reaction times (RTs) derived from the 3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 16 publications
10
38
0
1
Order By: Relevance
“…This pattern is in line with previous studies on the reliability of the emotional Stroop task in healthy subjects (Kindt et al, 1996;Siegrist, 1997;Eide et al, 2002;Strauss et al, 2005) which found low testeretest reliability scores for interference, but higher scores for response latency data. Those studies only reported testeretest reliability scores without investigating reliability for each single measurement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This pattern is in line with previous studies on the reliability of the emotional Stroop task in healthy subjects (Kindt et al, 1996;Siegrist, 1997;Eide et al, 2002;Strauss et al, 2005) which found low testeretest reliability scores for interference, but higher scores for response latency data. Those studies only reported testeretest reliability scores without investigating reliability for each single measurement.…”
Section: Discussionsupporting
confidence: 92%
“…Such a pattern of low reliability of the interference score (wÀ0.2 to 0.2) and high reliability of the response latencies (i.e. mean response latency emotional or neutral words; >0.80) has been replicated by more recent studies (Eide et al, 2002;Strauss et al, 2005). These reliability findings only apply to healthy subjects.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Interference scores of emotional stimuli from the Wrst half of each run were correlated with the interference scores from the second half. Split-half reliability amounted to 0.76 (Spearman-Brown corrected), which is above the reliability scores for emotional interference scores using a retest design with a 1-week interval (Eide et al 2002). Split-half reliability was 0.75 for negative and 0.65 for positive interference.…”
Section: Reaction Time Data and Error Ratesmentioning
confidence: 99%
“…Slower reaction times when naming font color indicate that word content is more accessible at implicit levels. (Eide, Kemp, Silberstein, Nathan, & Stough, 2002;Kindt, Bierman, & Brosschot, 1996;Siegrist, 1997;Strauss, Allen, Jorgensen, & Cramer, 2005) Predictive validity Validated by several research teams and shown to predict outcomes including mental health problems (Manschreck et al, 1988;Rikers, Loyens, Winkel, Schmidt, & Sins, 2005) Validated by several research teams and shown to predict outcomes including task performance, organizational citizenship behavior, and counterproductive work behavior Johnson & Lord, 2010;Steele & Aronson, 1995) Validated by several research teams and shown to predict outcomes including expectations for unfair treatment and mental health problems (Ritter, Fischbein, & Lord, 2006;Williams, Mathews, & MacLeod, 1996) Correlations with explicit measures Low (Rudman & Borgida, 1995) Moderate Low (Egloff & Schmukle, 2004;Payne, Binik, Amsel, & Khalife, 2004) Vulnerability Personality, affect (for reviews of prior uses, see MacLeod, 1991;Williams et al, 1996) Mode of administration Internal consistency .55 to .94 Internal consistency .69 (continued) (Karpinski & Steinman, 2006) Correlations with explicit measures Varies from low to high by domain …”
Section: A Functional Taxonomy Of Implicit Measuresmentioning
confidence: 99%